ڕە ههند ە گوزارشتگ هراییهكانی جهستهی ژن له پهیكهرسازی هه رێمی كوردستاندا (سلێمانی و ە ك نمونه) - محمد, پهری عبدالواحید (Sulaimani Journal for Humanities, 2021)
This research is entitled ((The dimensions of expressions in women's body in the Kurdistan region's sculpture, especially in Sulaimanyah)), and about finding a suitable example for the research's title, in the aim for practising to get the aftermath. The research includes four chapters. Chapter one is about selecting the overall investigation's frame which includes (Research's problem, its importance and the purpose, which is shedding light on the dimensions of expressions in women's body in the Kurdistan region's sculpture from 2002 to 2019 and contain idioms and concepts.) research problem starts with these questions: 1. Is women's aspect has affected dimensions of expressions in the Kurdistan region's sculpture? 2. How much they got useful in women's body in Kurdistan region sculpture? Chapter two is the theory frame of the research which discusses four inquests which are: Topic number one called (A. concept of expression, B. revolution of expression) This investigation is on the concept of expression. In the beginning, it gives the ideas of some ideologist about the concept, then the ideas of artists. Next, it talks about the expression revolution in terms of features, how it operates and embodiment in art expression in sculpture. Topic number two named (Women's body in the art of sculpture), this talks about the prehistoric and cultural ages as power age of women and historical epoch, . Later, examine how women's body was used in the modern art . Chapter three consists of the prosecutions ways of the research which is (Society's investigation, articles of gathering information, outline of the research, report analyzation). And some standards for explaining patterns which the researcher has chosen them to fit the research's aim in which obtained with women's body they are 3 examples. In chapter four, the researcher has accomplished some aims: 1. Women's body has been affecting the Kurdistan region's sculpture art as shown in all the examples. 2. Sculpturists use the expression style broadly, In the Kurdistan region's sculpture. 3. Sculpture in the Kurdistan region is built on social roots.